Developmental Crime Prevention Manifesto—or “Saving Children from a Life of Crime” 2.0: The 2024 David P. Farrington Lecture - Welsh, Brandon (Journal of developmental and life-course criminology, 2024)
Early developmental crime prevention is an important component of an overall strategy to reduce crime. Key features include a commitment to prevention in the first instance—intervening before a delinquent act has been committed and before a child has contact with the justice system—and a larger focus on improving the life chances of at-risk children and families, extending well beyond delinquency or criminal offending. The main aim of this article is to set out an agenda for action—a manifesto of sorts—to advance developmental crime prevention, with a special focus on the early stages of the life-course. Structured as a ten-point plan and organized around three core areas (policy directions, research priorities, and outreach), the agenda is designed to bring attention to what I view as the most important and pressing matters confronting early developmental crime prevention today. The good news is that the groundwork has been started on many fronts, with some successes and a great a deal of promise. David Farrington’s research and scholarly contributions figure prominently in this work, and this article also serves as a remembrance of David Farrington (1944–2024) and a way to celebrate his enduring life-work to help build a safer, more just society.